Inferior vena cava resection and reconstruction with a peritoneal patch for a leiomyosarcoma: A case report. (2020) - Risaliti, Matteo; Fortuna, Laura; Bartolini, Ilenia; Taddei, Antonio; Muiesan, Paolo
Highlights: Leiomyosarcoma of the inferior vena cava are very rare neoplasm with a limited responsiveness to medical therapy. Surgery seems to be the only chance of cure. Complex vascular resection are often necessary and required accurate reconstruction technique. Peritoneal patch is an efficient and safe option to repair venous defects and it is gaining great attention in recent years. Abstract: Introduction: Leiomyosarcomas (LMs) of the inferior vena cava (IVC) are very rare neoplasms seldom reported in the literature. The majority of patients does not present with specific abdominal pain and IVC LMs are used to become symptomatic with the increase of tumor volume. The role of chemotherapy or radiotherapy is not yet defined and surgical resection seems to be the only chance to improve survival rates. Presentation of case: We present a case of a 58-year-old female with a recent diagnosis of IVC LM who underwent surgery with a partial resection of the anterior wall of the vein using a lateral and partial vein clamping. The primary repair of the defect could result in stricture of the vein, so a parietal peritoneum patch was used for the vein reconstruction. The postoperative course was uneventful. Discussion: Actual evidence suggests that vascular sarcomas have limited responsiveness to cytotoxic chemotherapy and chemoradiotherapy, so surgery is the treatment of choice. Major surgery entailing multivisceral and complex vascular resection is usually necessary to achieve negative margins and accurate vascular reconstruction techniques are mandatory to avoid serious circulatory complications. Different kinds of graft (biological or synthetics) are available for the reconstruction, with intrinsic advantages and limitations. The use of peritoneal patches seems a valid and cheap option for vascular reconstruction and it is gaining great attention in recent years. Conclusion: This case demonstrates that peritoneal graft could be a safe option to manage IVC defects in expert hands. A brief review of literature is also included.